Conductive electrodes based on Ni–graphite core–shell nanoparticles for heterojunction solar cells - Kim, Chang-Duk (Elsevier Science, 2023)
Ni–graphite core–shell nanoparticles (CSNPs), which consisted of Ni nanoparticles (NPs) wrapped with several graphene layers, were grown by the thermal reduction of NiO NPs using H2. The effect of the synthesis temperature (800, 900, 1000, and 1100 °C) on the formation of multilayer graphene shells on the Ni core NPs was investigated to evaluate the structural and electrical characteristics of the particles. The proposed chemical reactions for the formation of Ni NPs can be summarized as follows: formation of liquid Ni by the reduction of NiO, thermal decomposition of the NiO phase, and formation of multilayer graphene shell because of the supersaturation of C in the liquid Ni phase. The resistivity of the electrode pattern fabricated with the Ni–graphite CSNP paste was found to be 6.75 × 10−3 Ω•cm. Further, the power conversion efficiency of bulk heterojunction solar cells fabricated with the Ni–graphite CSNPs is higher than that of cells fabricated without the Ni−graphite CSNPs. Thus, our Ni–graphite CSNPs can be employed as a highly efficient electrode material in bulk heterojunction solar cells.